2017
DOI: 10.2217/fmb-2017-0013
|View full text |Cite
|
Sign up to set email alerts
|

Immune Escape Strategies of Borrelia Burgdorferi

Abstract: The borrelial resurge demonstrates that Borrelia burgdorferi is a persistent health problem. This spirochete is responsible for a global public health concern called Lyme disease. B. burgdorferi faces diverse environmental conditions of its vector and host during its life cycle. To circumvent the host immune system is a prominent feature of B. burgdorferi. To date, numerous studies have reported on the various mechanisms used by this pathogen to evade the host defense mechanisms. This current review attempts t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 156 publications
0
9
0
Order By: Relevance
“…Immune evasion strategies used by Borrelia to establish infection have been extensively reviewed elsewhere [35,[156][157][158][159][160][161][162][163]. Thus, the detailed biochemistry of host subversion is beyond the scope of this communication.…”
Section: Immune Modulationmentioning
confidence: 99%
“…Immune evasion strategies used by Borrelia to establish infection have been extensively reviewed elsewhere [35,[156][157][158][159][160][161][162][163]. Thus, the detailed biochemistry of host subversion is beyond the scope of this communication.…”
Section: Immune Modulationmentioning
confidence: 99%
“…These serological tests are indirect diagnostic methods measuring the presence of anti- Bb antibodies (Abs) [ 25 ]. Unfortunately, these techniques have many limitations [ 26 ]. Bb sl is able to escape the immune system according to a large variety of mechanisms, inducing a reduced immune protection despite the activation of innate and adaptive immunity [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genome comparisons further revealed that lipoprotein-encoding genes are the most variable loci within the genome, consistent with their roles in evading vector and host immunity [14]. For example, B. burgdorferi shifts its surface lipoprotein composition when migrating between the tick vector and the mammalian host, up-regulating the expression of outer surface protein A (OspA) during tick colonization, the expression of OspC during host invasion, and the expression of VlsE (Variable membrane protein-Like Sequence E) during persistency within the host [15,16].…”
Section: Antigenic Variations In Lyme Disease Pathogensmentioning
confidence: 91%